2006 International RF and Microwave Conference 2006
DOI: 10.1109/rfm.2006.331084
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Post-ADC Digital Beam-Forming for Large Area Radar Receiver Arrays

Abstract: In order to provide instantaneous three-dimensional radar measurements spanning the entire vertical extent of the ionosphere, the planned EISCAT 3D incoherent scatter radar system includes multiple receive-only antenna arrays, situated at 90-280 km from the main transmit/receive site. These will employ band-pass sampling at ∼80 MHz, with the input signal spectrum contained in the 6 th Nyqvist zone. This paper presents simulations and methods used to investigate use of a post-ADC fractional-sample-delay (FSD) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…If the reference element is assumed to be unaffected by the environment the term will be known, with and given by (5). The only remaining unknowns are then the constants .…”
Section: B the Difference Between Two Antennas In An Antenna Arraymentioning
confidence: 99%
See 2 more Smart Citations
“…If the reference element is assumed to be unaffected by the environment the term will be known, with and given by (5). The only remaining unknowns are then the constants .…”
Section: B the Difference Between Two Antennas In An Antenna Arraymentioning
confidence: 99%
“…Assuming that there is a linear change of between time and , the state is related to the previous state with (18) where (19) where is the identity matrix and is the time between and . Further, the observations, at time can then be related to the state using (20) where is the noise and (21) where is given by (5). The Kalman filter uses the previous state and the observations to estimate the current state .…”
Section: B Kalman Filtermentioning
confidence: 99%
See 1 more Smart Citation
“…Since the system will be multistatic and each antenna array will have narrow beams, it is crucial to have accurate control over the pointing direction and shape of the beam from the array. It has been found that the maximum acceptable delay error between any two antenna elements is 160 ps [6]. This limit includes all errors such as jitter in the local oscillator and in the analog-to-digital converter (ADC), errors introduced in the clock distribution system, changes in the phase of the far-field pattern of the antenna elements, and changes in the physical position of the antenna elements.…”
Section: Introductionmentioning
confidence: 99%